1975
DOI: 10.1079/bjn19750023
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent studies of the flow of digesta in the duodenum and of exocrine pancreatic secretion of calves

Abstract: I. The flow of digesta through the duodenum and the concurrent secretion of the pancreas were studied in four Friesian calves given four milk-substitute diets. The diets were: reconstituted, 'mildly' pre-heated, spray-dried skim-milk powder with (SKF) or without (SK) margarine fat or with 5 0 yo of the skim-milk powder in diet S K F replaced by soya-bean flour (ASKF) or fish-protein concentrate (BSKF), together with dried whey. The diets were given ad lib. twice daily from 13 to 37 d of age, each diet being gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…Net secretary contributions to total abomasal digesta from gastric and salivary sources did not change greatly in calves aged between 30-60 and 80-120 d ( Table 2). This observation is consistent with estimates of apparent salivary and abomasal secretion measured at the duodenum of calves during 12 h after feeding whole milk reported by Ternouth, Roy & Shotton (1976). These workers found that total amounts of apparent secretion did not differ with age when related to whole milk intake.…”
Section: Discussionsupporting
confidence: 91%
“…Net secretary contributions to total abomasal digesta from gastric and salivary sources did not change greatly in calves aged between 30-60 and 80-120 d ( Table 2). This observation is consistent with estimates of apparent salivary and abomasal secretion measured at the duodenum of calves during 12 h after feeding whole milk reported by Ternouth, Roy & Shotton (1976). These workers found that total amounts of apparent secretion did not differ with age when related to whole milk intake.…”
Section: Discussionsupporting
confidence: 91%
“…Associated with the marked decrease in susceptibility to enteric infections as calves grow older (88,106) is an increase in gastric acid production and in digestibility of protein (174). However, differences exist between breeds in their susceptibility to enteric and respiratory infections.…”
Section: Genetic Environmentmentioning
confidence: 99%
“…Thus, the amount of colostral antibody that reaches the neonatal blood stream depends not only on management but also on genetic attributes of both mother and offspring (163). Breed differences in digestive efficiency of postcolostral diets (144) may be due to differences in amounts of digestive enzymes (174). A breed difference in susceptibility to rotavirus also has been suggested (2).…”
Section: Genetic Environmentmentioning
confidence: 99%
“…Friesian and Jersey calves have been shown to have a higher efficiency of absorption of Ig than have Red Danish calves (Kruse, 1970) and Friesian × Ayrshire calves were more efficient than Ayrshires in absorbing Ig from Ayrshire colostrum (Seiman et al, 1971b) and Holsteins were more efficient than Ayrshires in absorbing total Ig from Holstein colostrum (Baumwart et al, 1977). Breed differences in efficiency of digestion of post-colostral diets (Roy et al, 1970) may be due to differences between breeds in the amounts of digestive enzymes (Ternouth et al, 1976). Associated with the marked decrease in susceptibility to enteric infections as calves grow older is an increase in gastric acid production and in digestibility of protein (Ternouth et al, 1976).…”
Section: Innate Resistancementioning
confidence: 99%
“…Breed differences in efficiency of digestion of post-colostral diets (Roy et al, 1970) may be due to differences between breeds in the amounts of digestive enzymes (Ternouth et al, 1976). Associated with the marked decrease in susceptibility to enteric infections as calves grow older is an increase in gastric acid production and in digestibility of protein (Ternouth et al, 1976).…”
Section: Innate Resistancementioning
confidence: 99%